First-Principles Investigation of the Electronic and Optical Properties of Tin Chalcogenides (SnS, SnSe and SnTe) Using Density Functional Theory - Kagara, Salihu Ibrahim; Yakubu, Abubakar; Aliero, Yahaya Abubakar; Abdullah, Sirajo (FUDMA Journal of Sciences, 2026)
We have studied the electrical and optical properties of SnA (A = S, Se, Te) through first-principles calculations within Density Functional Theory (DFT) as implemented in Quantum ESPRESSO. The Generalised Gradient Approximation (GGA) was exchange-correlation is used in form of Perdew-Burke-Ernzerhof (PBE) and Perdew-Burke-Ernzerhof for solids (PBESol). The study shows different trends in the electronic behaviour of the Chalcogenides: SnS is a semiconductor with a low direct band gap (0.186 and 0.087 eV for both PBE and PBESol) while SnSe and SnTe have metallic behaviours with zero band gap this could be due to the well-known underestimation of band gaps by standard GGA approximations and the lack of spin-orbit coupling effects. The optical properties such as complex dielectric function, refractive index, absorption coefficient, energy loss function, extension coefficient and reflectivity are calculated. The peak of the dielectric function is red shifted from SnS to SnTe.The SnS refractive index with PBE has high static values (n = 3.3). The onset of the PBE optical absorption is at around 1.5 eV for SnS and 1.0 eV for SnTe. The energy loss function of SnTe exhibits a strong plasmon peak and good optical conductivity. The results show consistent red-shift in the absorption edges and improvement in optical conductivity from SnS to SnTe compared to the decrease in band gap. SnSe and SnTe have a very strong metallic-like optical response which suggest the possibility for infrared optoelectronic devices whereas SnS shows promising absorption in the visible to infrared region suitable for photovoltaic applications.
Keywords: Tin Chalcogenides; Density Functional Theory; Band Gap; Photovoltaic Materials; Infrared Optoelectronics